ANALISIS KINERJA KEUANGAN ORGANISASI NIRLABA (STUDI KASUS YAYASAN PUNDI AMAL PEDULI KASIH TAHUN 2018-2021): Studi Kasus Yayasan Pundi Amal Peduli Kasih Tahun 2018-2019 - ema yohana br sinambela; Ni Luh Gede Erni Sulindawati (Universitas Pendidikan Ganesha, 2026)
This study aims to analyze the financial performance of the non-profit organization Yayasan Pundi Amal Peduli Kasih for the period 2018–2021. The method used is a descriptive quantitative approach through the analysis of non-profit organization financial ratios using secondary data from the foundation's annual financial reports. The results show that fiscal performance ratio 1 fluctuated, while fiscal performance ratio 2 showed a downward trend with negative values in the last three years, indicating an operational deficit. Public support ratio 1 was at a very high and stable level in the range of 0.98–0.99, reflecting dependence on voluntary funds, while public support ratio 2 was fluctuating. The fund collection efficiency ratio shows efficient performance with a value above 1.00 every year, and the program efficiency ratio is in the range of 0.95–1.00. Revenue growth during the study period shows unstable conditions. These findings confirm the need to strengthen financial management strategies and diversify funding sources to maintain organizational sustainability.